2010
DOI: 10.4097/kjae.2010.58.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketamine versus thiopental sodium anesthetic induction and a small dose of fentanyl on emergence agitation after sevoflurane anesthesia in children undergoing brief ophthalmic surgery

Abstract: BackgroundEmergence agitation (EA) in children after sevoflurane anesthesia is common. The purpose of this study was to compare the incidences of EA between ketamine and thiopental sodium induction in children underwent sevoflurane anesthesia. We also evaluated if a small dose of fentanyl could reduce the incidence of EA.MethodsThe patients who were scheduled for strabismus or entropion surgery were divided into 4 groups. The patients in Groups 1 and 2 were induced anesthesia with ketamine 1.5 mg/kg; those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Thus, repeated assessments in this study revealed a higher incidence of EA in the ketamine group despite the slower awakening. A study comparing the incidence of EA in children after short sevoflurane anesthesia with induction of 5 mg/kg thiopental and 1.5 mg/kg of ketamine showed no difference [11]. The incidence of EA in the study was comparable to our results, suggesting anesthetic induction with standard dose of ketamine is not suitable for reducing EA.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, repeated assessments in this study revealed a higher incidence of EA in the ketamine group despite the slower awakening. A study comparing the incidence of EA in children after short sevoflurane anesthesia with induction of 5 mg/kg thiopental and 1.5 mg/kg of ketamine showed no difference [11]. The incidence of EA in the study was comparable to our results, suggesting anesthetic induction with standard dose of ketamine is not suitable for reducing EA.…”
Section: Discussionsupporting
confidence: 57%
“…For the trials that compared a control group with multiple intervention groups using different fentanyl doses, we combined the intervention groups to conduct a single pair-wise comparison. Single fentanyl administration was performed in 15 trials [ 4 , 12 , 43 – 47 , 49 – 56 ], and continuous infusion was carried out in 1 trial [ 48 ]. Five studies were performed in the USA [ 12 , 46 , 53 55 ], three in Egypt [ 43 , 47 , 56 ], two each in Korea [ 44 , 49 ] and Turkey [ 50 , 52 ], and one each in Italy [ 4 ], China [ 45 ], Japan [ 48 ] and Saudi Arabia [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The blinding of participants and personnel, the blinding of the outcome assessment, the presence of incomplete outcome data, and selective reporting were determined to be at a low risk of bias in all included studies. Random sequence generation was unclear in five trials [ 45 , 47 , 49 , 51 , 53 ], and allocation concealment was unclear in 14 studies [ 4 , 12 , 43 , 44 , 46 , 48 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, pain can be difficult to assess in preverbal children and may mimic the signs of EA, making it difficult to differentiate EA from postoperative pain. Although intravenous [10,25] or intranasal fentanyl [9] and dexmedetomidine [26,27] are effective in treating both pain and EA, the exact role of pain in the etiology of EA remains unclear. Although ketamine, fentanyl, and dexmedetomidine are known medications in preventing EA, a subgroup analysis of preoperative analgesia found that their analgesic effects had no influence on the efficacy of the drugs on EA [23].…”
Section: Discussionmentioning
confidence: 99%